2013
DOI: 10.1073/pnas.1310215110
|View full text |Cite
|
Sign up to set email alerts
|

Superior induction and maintenance of protective CD8 T cells in mice infected with mouse cytomegalovirus vector expressing RAE-1γ

Abstract: Due to a unique pattern of CD8 T-cell response induced by cytomegaloviruses (CMVs), live attenuated CMVs are attractive candidates for vaccine vectors for a number of clinically relevant infections and tumors. NKG2D is one of the most important activating NK cell receptors that plays a role in costimulation of CD8 T cells. Here we demonstrate that the expression of CD8 T-cell epitope of Listeria monocytogenes by a recombinant mouse CMV (MCMV) expressing the NKG2D ligand retinoic acid early-inducible protein 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 38 publications
(37 reference statements)
1
44
0
Order By: Relevance
“…Chimeric antigen receptors expressing the extracellular domain of NKG2D linked to the signaling elements of CD3ζ and DAP10 have been constructed and transduced into T cells to test their potential for cancer therapy (reviewed in (77)). As therapeutics in infectious disease, Jonjic and colleagues have introduced a cDNA encoding a NKG2D ligand into the mouse CMV genome and showed that it functions as an effective vaccine for CMV (78). These findings suggest a new strategy for the development of vaccines against pathogens that have been refractory to conventional approaches.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…Chimeric antigen receptors expressing the extracellular domain of NKG2D linked to the signaling elements of CD3ζ and DAP10 have been constructed and transduced into T cells to test their potential for cancer therapy (reviewed in (77)). As therapeutics in infectious disease, Jonjic and colleagues have introduced a cDNA encoding a NKG2D ligand into the mouse CMV genome and showed that it functions as an effective vaccine for CMV (78). These findings suggest a new strategy for the development of vaccines against pathogens that have been refractory to conventional approaches.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…Accordingly, genetically modified animal CMVs lacking immunoevasins exhibited outstanding vaccine properties in mouse and guinea pig models [30, 31]. Recently, we found that a mouse CMV (MCMV) expressing a host ligand for the activating receptor NKG2D induces an efficient CD8+ T cell response despite being profoundly attenuated [15, 32]. Moreover, challenge infection experiments indicated that the protection obtained after immunization is superior to the one seen after natural infection [15, 32].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, replacement of m152 with the murine NKG2DL Rae-1 increased CD8 + T cell responses to MCMV [19, 20]. This is in stark contrast to the complete absence of T cell responses observed in CMV-naïve animals inoculated with ΔRh159.…”
Section: Discussionmentioning
confidence: 99%